Coupled Coincidence Point Theorem in Partially Ordered Metric Spaces via Implicit Relation - Nguyen Manh Hung; Erdal Karapınar; Nguyen Van Luong (Abstract and Applied Analysis)
We prove a coupled coincidence point theorem for mappings F : 𝑋×𝑋→𝑋 and g : 𝑋→𝑋, where F has the mixed g-monotone property, in partially ordered metric spaces via implicit relations. Our result extends and improves several results in the literature. Examples are also given to illustrate our work.